The Influence of Return on Equity, Current Ratio, and Price Earnings Ratio on Stock Prices in Mining Sector Companies in 2019-2022 Listed on the Indonesian Stock Exchange - Hidayat, Cakra; Hikmah, Khoirul; Pujiharjanto, Colombanus Ambar (Strata Social and Humanities Studies, 2023)
The purpose of this study is to collect empirical information concerning the factors of return on equity, price-earnings ratio, and current ratio as they relate to the pricing of stocks. In this study, a quantitative approach was combined with secondary data. Companies that are active in the mining sector and are listed on the Indonesia Stock Exchange make up the population of companies that are the focus of this research. In addition, the current population was studied to identify the sample through the use of purposive sampling, and a total of 8 companies were collected between the years 2019 and 2022. The hypothesis put up in this investigation was put to the test by employing multiple regression analysis and the software version 25 of SPSS. According to the findings of the study, both the return on equity and the current ratio had a good and significant impact on stock prices. Furthermore, both of these factors had a positive and significant influence on stock prices. In contrast, the price-earnings ratio had a negative influence on share prices, although it did not have any meaningful impact overall.